Embodied Negotiation: Preparing Future Lawyers Through Integrative Practice - Malin Stearns Johnson; Carolyn Wilkes Kaas; Kara Perry; J. Kim Wright (Washington University Journal of Law and Policy, 2026)
The legal profession is changing rapidly: accelerating technological change, political pressure and polarization, and a documented crisis to lawyer well-being. Legal pedagogy must prepare future lawyers for the uncertain world that lies before them. Gone are the days where educators must rely on doctrines and skills alone. There must be a shift in priority – we must foster human-centered capacities essential for these times of uncertainty. This article introduces the Integrative Law Approach to Negotiation course, a course designed to frame negotiation as a relational, values-based practice with a real-world application that supports students in developing their presence, empathy, and well-being. Fit with well-being plans, reflection essays and weekly journals, group assessments, the course provides students an opportunity to develop and improve their professional identity while continuously evaluating their well-being. The program has also evolved to address the changing American Bar Association (“ABA”) guidelines for legal education, the continuing development and proliferation of AI, and current threats to democratic institutions. As the world and legal industry changes, this course aims to meet those changes, and foster student growth, head on.
Keywords: #IntegrativeLaw; #LegalPedagogyReform; #ValuesBasedPractice; #ReflectiveLawyering; #NegotiationAsRelational; #EmpathyInLaw; #HumanCenteredLawyering; #TeachingThroughUncertainty